The ergogenic effect of caffeine on cycling time trial performance is not influenced by a common polymorphism in the ADORA2a gene in male cyclists: A pilot study - Lynn, A.; Ong, S. P.; McKitton, L.; Oliver, L.; Ranchordas, M.; Nichols, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
It is well established that caffeine supplementation can enhance endurance exercise performance. However, inter-individual variability in the ergogenic effect of caffeine has been reported. This variability has not been adequately explained, but could reflect differences in habitual caffeine intake, training status, or age. Common genetic polymorphisms in genes encoding proteins involved in the metabolism and physiological actions of caffeine may also be important. A functional single nucleotide polymorphism (SNP) in the adenosine A2a receptor gene (ADORA2a; 1976 T>C; rs5751876) has been reported to influence the ergogenic response to caffeine. In women undertaking a 10 min time-trial, caffeine ingestion improved performance in all women with a T/T genotype (n=6), whereas in those carrying a C allele, performance only improved in one of six participants. Only 10 to 20% of the population have a T/T genotype, so a lack of effect of caffeine in those with a C allele seems improbable. Thus, the aim of the current study was to further explore the effect of the ADORA2a 1976 T>C SNP on the ergogenic effect of caffeine. Trained cyclists (n=23; age 38 (SD 11) y, mass 71.7 (SD 12.3) kg, BMI 22.9 (SD 2.3) kg/m2, VO2 max 60.7 (SD 10.8) ml/kg/min) completed a randomised cross-over trial. Each participant completed a VO2max test, and 3 x 16 km time trials (1 x familiarisation and 2 x experimental trials) on a cycle ergometer. Caffeine (3 mg/kg) or placebo was consumed 60 min before the experimental time trials. The effect of caffeine on performance and interaction with genotype was assessed with a mixed model ANOVA. Caffeine caused a 1% decrease in time trial time (-15.1 s, 95% CI, -24.9, -5.3; p=0.016). There was no significant interaction between ADORA2a genotype and change in 16 km time when participants were split into 3 genotypes (TT (n=5), CT (n=4) and CC (n=14); p=0.928) or grouped based on the presence of a C or T allele (TT v CT/CC combined; p=0.715; CC v CT/TT combined; p=0.896). Moreover, the magnitude of the decrease in time was similar for each genotype (CC = 15.6 s; CT = 17.5 s, TT = 11.7 s). In the present study there was no indication that a common functional SNP in the ADORA2a gene modifies the ergogenic effect of a moderate dose of caffeine on 16 km cycling time-trial performance in trained male cyclists.